Inequality of Opportunity and Income Redistribution - Marcel Preuss; Germán Reyes; Jason Somerville; Joy Wu (Center for Economic Studies and ifo Institute (CESifo), 2023)
We examine how people redistribute income when there is uncertainty about the role luck plays in determining opportunities and outcomes. We elicit redistribution decisions from a U.S.-representative sample who observe worker outcomes and whether luck magnified workers' effort ("lucky opportunities") or determined workers' income directly ("lucky outcomes"). We find that participants redistribute less and are less reactive to changes in the importance of luck in environments with lucky opportunities. Our findings have implications for models that seek to understand and predict redistribution attitudes, and help to explain the gap between lab evidence on support for redistribution and U.S. inequality trends.
Keywords: C91; D63; 330; inequality of opportunity; fairness; luck; perceptions